Securitization of migration and the far right: the case of Greek security professionals. (8th December 2015) - Lazaridis, Gabriella; Skleparis, Dimitris
Abstract: Since the events of 9/11, security concerns have gained unprecedented dominance on western governments' national and international political agendas; Greece has been no exception. The success or failure of a far right party, like Golden Dawn, depends on the effectiveness of the government to regulate immigration and to develop policies aimed at combating the racism which pervades the political culture of society at this particular juncture, when the country is experiencing severe crisis. The aim is to provide an account of the rationale of the securitization of migration from the perspective of Greek security professionals. We argue that the extreme securitizing perceptions of security professionals have been exploited and assisted by far‐right extremist groups, which instilled racial violence, hate speech/crime into society, resulting in patterned, unreflective, and routinized security practices and discourses which are more in line with the beliefs and values advocated by the extreme right.